Bird Composition and Diversity in the Area Where the Green Larat Orchid (Dendrobium capra) Was Found at the Dodol Forest Management Unit (RPH-Dodol), Bojonegoro - Dwi Oktafitria; Laily Agustina Rahmawati; Roso Satriyo; Ahmad Niamul Abrori (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
Dendrobium capra, an endangered epiphytic species, depends on complex ecological interactions within teak forests. Birds play multifaceted roles: as potential pollinators through ornithogamy, pest control agents maintaining host tree health, seed dispersers for host trees, and habitat quality indicators. Conservation efforts for Dendrobium capra must prioritize bird community preservation to ensure ecological functions supporting this endemic Javanese orchid's life cycle. This study, conducted January–March 2026 using field surveys with point count technique at purposively selected observation points, documented bird and Dendrobium capra presence in natural habitat. Observations recorded 363 individual birds comprising 49 species, 36 genera, 21 families, and 11 orders. The dominant species was Passer montanus; Cisticolidae had the most species; Passeriformes was most abundant. The Shannon-Wiener diversity index of 3.52 indicates high diversity; Simpson dominance index of 0.038 indicates no dominant species (even individual distribution among species, showing ecological balance); Pielou evenness index of 0.905 indicates very even distribution across species. This ecologically reflects a stable habitat supporting diverse species evenly. These results indicate good habitat quality, important to preserve as conservation habitat for birds and Dendrobium capra. A diverse, stable bird population benefits Dendrobium capra by indicating a functioning habitat, maintaining ecosystem stability, and supporting ecological conditions required by this epiphytic orchid. Future research will compare bird populations across seasons to understand temporal dynamics of these ecological interactions.